The Palgrave Handbook of EU Crises
XXI, 796 p. 16 illus., 10 illus. in color.
Keywords: This handbook comprehensively explores the European Union’s institutional and policy responses to crises across policy domains and institutions – including the Euro crisis, Brexit, the Ukraine crisis, the refugee crisis, as well as the global health crisis resulting from COVID-19. It contributes to our understanding of how crisis affects institutional change and continuity, decision-making behavior and processes, and public policy-making. It offers a systematic discussion of how the existing repertoire of theories understand crisis and how well they capture times of unrest and events of disintegration. More generally, the handbook looks at how public organizations cope with crises, and thus probes how sustainable and resilient public organizations are in times of crisis and unrest. Marianne Riddervold is Professor in Political Science at the Inland Norway University of Applied Sciences and the Norwegian Institute of International Affairs (NUPI), and Senior Fellow at the Institute of European Studies, University of California, Berkeley, USA. Jarle Trondal is Professor of Political Science at the Department of Political Science and Management, University of Agder, and Professor of European Studies at the ARENA Centre for European Studies, University of Oslo, Norway. Akasemi Newsome is Associate Director at the Institute of European Studies and Executive Director at the Peder Sather Center for Advanced Study, University of California, Berkeley, USA, and Senior Fellow at the Inland Norway University of Applied Sciences.